2022
DOI: 10.1038/s41598-022-12640-4
|View full text |Cite
|
Sign up to set email alerts
|

Indirect organogenesis for high frequency shoot regeneration of two cultivars of Sansevieria trifasciata Prain differing in fiber production

Abstract: Sansevieria trifasciata is used as an indoor plant, in traditional medicine and as a fiber source. Here we characterized fibers of two of varieties of S. trifasciata, Lorentii and Hahnii, and report a protocol for their propagation based on indirect shoot organogenesis. Structural and ribbon fibers were scattered within leaf parenchyma when viewed with confocal laser scanning microscopy. Chemical analysis of the fibers by mass spectrometry and high-performance chromatography revealed higher contents of cellulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Mass propagation through in vitro procedures has been investigated as a solution to address the increasing commercial demand. Recently, direct and indirect organogenesis from leaf explants have been reported for S. trifasciata and S. masoniana [3,[10][11][12]. Here we report for the first time, to the best of our knowledge, a technique for plant regeneration starting from flower explants.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Mass propagation through in vitro procedures has been investigated as a solution to address the increasing commercial demand. Recently, direct and indirect organogenesis from leaf explants have been reported for S. trifasciata and S. masoniana [3,[10][11][12]. Here we report for the first time, to the best of our knowledge, a technique for plant regeneration starting from flower explants.…”
Section: Introductionmentioning
confidence: 86%
“…is a genus of succulent plants with approximately 90 distinct species identified [1], originally found in tropical central Africa and drier parts of eastern and southern Africa [2]. Sansevieria plants are cultivated for medicinal, fodder, soil conservation and fiber uses [3]. Recently it has been reported that Sansevieria plants have also a high capacity to reduce environmental pollution produced by gases and heavy metals thanks to the ability to absorb hazardous pollutants such as VOCs and CO 2 emissions [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…A histological analysis of the chronological sequence of morphological events during ontogeny is a way to know what morphogenic process was induced (Delporte et al, 2014). Somatic embryogenesis and/or organogenesis has been described and confirmed using histological analysis in different species (Delgado-Aceves et al, 2021;Mamgain et al, 2022;García-Hernández et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Other investigational leads explore interactions with microbionts which variously augment resilience attributes in these plants 82 – 85 . Research in the genus Sansevieria however witnesses a slow pace in current developments majoring only with its phytochemical 73 75 and fiber reserves 86 . Recent literature depicts a recessed trend of investigations especially those warranted on various stressors and mechanisms that allow survivability of Sansevieria plants.…”
Section: Introductionmentioning
confidence: 99%